2008
DOI: 10.5704/moj.0811.010
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of Comminuted Patellar Fracture with Combined Cerclage and Tension Band Wiring Technique

Abstract: In comminuted patellar fractures, a combination of cerclage wiring and tension band fixation is said to provide good mechanical stability. This is a retrospective review of four patients treated with this method. All fractures described herein were classified as 45-C3 (based on Orthopaedic Trauma Association classification) and were fixed with a 1.25mm cerclage wire and tension band wire proximally looped through the quadriceps tendon and distally through the patellar ligament in a figure-of-eight configuratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 4 publications
(3 reference statements)
1
11
0
Order By: Relevance
“…Circumferential cerclage wiring added to the TBW has been regarded to improve the strength of the construct by some researchers. [17][18][19] Curtis, in a cadaveric study, concluded that the addition of cerclage wiring to the TBW significantly adds to the strength of the construct. 20 In present study, on the basis of inclusion and exclusion criteria, authors studied 54 cases of displaced transverse fractures of the body of patella from June 2017 to December 2018.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circumferential cerclage wiring added to the TBW has been regarded to improve the strength of the construct by some researchers. [17][18][19] Curtis, in a cadaveric study, concluded that the addition of cerclage wiring to the TBW significantly adds to the strength of the construct. 20 In present study, on the basis of inclusion and exclusion criteria, authors studied 54 cases of displaced transverse fractures of the body of patella from June 2017 to December 2018.…”
Section: Discussionmentioning
confidence: 99%
“…16 Although, TBW is the current gold standard for the displaced transverse patella fractures, few surgeons recommend augmentation of TBW with circumferential cerclage wiring to enhance the strength of the fixation. [17][18][19] Authors planned present study to compare the results of the displaced transverse patella fractures managed using TBW and circumferential cerclage wiring with the ones treated by TBW alone.…”
mentioning
confidence: 99%
“…Patellar fractures are common and it constitutes about 1% of all skeletal injuries resulting from either direct or indirect trauma. 1,2 The subcutaneous location of the patella makes it vulnerable to direct trauma, whereas violent contraction of the quadriceps results in indirect fractures of the patella. These fractures are usually transverse and are associated with tears of medial or lateral retinaculum.…”
Section: Introductionmentioning
confidence: 99%
“…Fracture fixation is an alternative to excision for treatment of comminuted inferior pole fractures to obtain an accurate reduction, rigid fixation and to restore the knee extension mechanism which allows early range of motion. However this is usually difficult to achieve due to the high degree of comminution of these fractures [10] .…”
Section: Disscusionmentioning
confidence: 99%
“…Figure of eight wiring of the patella and tibia to protect the repair of Patellar tendon is an option but this caries the risk of breakage of the wire loop. Also the wire loop may cause anterior knee joint pain because of the tenting during knee movement [10] .…”
Section: Disscusionmentioning
confidence: 99%